New Product Development from Radish of Ban Phayom Community, Wang Noi district, Phra Nakhon Si Ayutthaya province, Thailand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper aims to develop new products from the radish, Ban Phayom community, Wang Noi District, Phra Nakhon Si Ayutthaya Province which is operated using a Qualitative Research process and Participatory action research (PAR). The operating was (1) In-depth interviews and data collection from 50 citizens and stakeholders in the Phayom community, (2) A group meeting to brainstorm and analyze a SWOT from Participatory action research (PAR), which uses a process of involvement by the community and associated networks. The research was found that: (1) the community market survey found that there is a need to transform radish products, which want to modernize packaging design, be able to sell products to different groups of customers, and develop distribution channels to be able to sell products in multiple channels. (2) the community opinions, brainstorming, and analyzing SWOT in order to create a plan for developing new products to truly meet the needs of all groups of customers. (3) the producing a prototype product, it was found that the community has tried to transform radish products to be up to date with the current era and to improve their ingredients and materials to meet the needs of new target customers who have developed new products. was the Korean pickled radish. (4) Market testing, it was found that the community had put the product on sale at the community flea market before improving the product to be sold. (5) the sales were found that the community has developed Korean pickled radish products to be sold both offline and online, which are sold at stores in the Phayom community and on the Facebook page of Phayom Community Products.